The Role of Competence and Competent In Preparing Professional Training Teachers For Professional Activity - Oybek Daminov, Bekmurat Tulaev, Dustnazar Khimmataliev, Vyacheslav Shakov, Zuhra Kurbonova (International Journal of Advanced Science and Technology, 2020)
The article describes the role and place of competence and competent in the system of professional training of future teachers of vocational education. The essence of the concepts of "competence", "competent", "basic competence", "professional competence" is revealed on the basis of the results of scientific research conducted by scientists and researchers around the world, including authors. It is important that students constantly enrich their knowledge, learn new information, feel the requirements of the time, seek new knowledge, process it and apply it in their practical activities in the formation and improvement of professional competencies. Existing psychological and pedagogical research on the formation of professional and basic competencies in future vocational education teachers and the existing contradictions in the specialized literature are covered. Substantiation of a set of professional competencies based on the analysis of pedagogical conditions, methods and tools of the educational process for the training of future teachers of vocational education, determination of the list of general and specialized disciplines in which professional competencies are formed, pedagogical methodology of the organization of educational process allowing effective and sustainable formation comes, ensuring the formation of the basic competence of the students, and supporting the development of educational and methodical complex, it has been proved that it is possible to form professional basic competencies through the design stages of methods and tools for assessing the level of formation of professional basic competencies in students.